Investigasi Struktur dan Energi Band Gap Partikel Nano Tio2 Hasil Sintesis Menggunakan Metode Sol-Gel - Anita Listanti; Ahmad Taufiq; Arif Hidayat; Sunaryono Sunaryono (JPSE (Journal of Physical Science and Engineering), 2018)
TiO2 is a semiconductor material that widely applied in various fields due to its superiority both in terms of physical and chemical properties. In this study, the TiO2 nanoparticles was synthesized using sol-gel method. The synthesis of TiO2 nanoparticles was started by reacted TiCl3 with aquades and titrated with ammonium hydroxide and then followed by calcination process at 600 0C for 1.5 hours. The structural characteristics were investigated using XRD. The fungsional groups of the TiO2 nanoparticles were characterized by FTIR. The optical properties of the TiO2 nanoparticles were determined using UV-Vis spectrometer. The morphology of the sample was characterized using SEM. The results show that the TiO2 has structure as anatase phase. The data analysis using the Scherrer’s equation show that the particle crystallite size of is about of 9.77 nm. The energy band gap value of the TiO2 is 3.28 eV. Based on the SEM image, the agglomeration of the sample was formed with the average diameter of particle size of TiO2 is about 92 nm.DOI: http://dx.doi.org/10.17977/um024v3i12018p008